Eosinophilic Renal Cell Tumors With a TSC and MTOR Gene Mutations Are Morphologically and Immunohistochemically Heterogenous: Clinicopathologic and Molecular Study. (July 2020) - Tjota, Melissa; Chen, Heather; Parilla, Megan; Wanjari, Pankhuri; Segal, Jeremy; Antic, Tatjana
Abstract : Eosinophilic renal neoplasms have a wide spectrum of histologic presentations, and several studies have demonstrated a subtype of renal cell carcinomas (RCCs) associated with the tuberous sclerosis complex (TSC)/mammalian target of rapamycin pathway. A review of our institutional archives led to the identification of 18 cases of renal eosinophilic tumors with unusual morphology. Immunohistochemical analysis demonstrated that these could be separated into 3 groups: group 1 had solid architecture and morphology similar to chromophobe RCC but was negative for CK20 and vimentin, and had weak focal staining for CK7 and P504S; group 2 had solid architecture and morphology similar to either renal oncocytoma or chromophobe RCC, eosinophilic variant and had diffuse staining of CK7 and P504S, absent to weak staining of CK20, and negative staining for vimentin; and group 3 had solid, cystic and papillary architecture and was negative for CK7, except for 1 case, along with moderate to strong staining of CK20, P504S, and vimentin. The cases were then sent for next-generation sequencing to determine whether molecular pathogenic variants were present. In group 1, all 3 cases had mutations in TSC2 . In group 2, pathogenic variants were identified in 3 genes: TSC1, TSC2, and MTOR . In group 3, genetic alterations and pathogenic variants were identified in TSC1 and TSC2 . Our results support TSC/MTOR-associated neoplasms as a distinct group that exhibits heterogenous morphology and immunohistochemical staining.